Employment Determination in a Unionized Public-Sector Labor Market: The Case of Ontario's School Teachers - Currie, Janet (Journal of Labor Economics, 1991)
A standard efficient-contracts model of employment determination in a unionized labor market is contrasted with a naive model of labor supply and demand that allows for the possibility of monopsony in the market for public school teachers. The standard model is consistent with the data and suggests that employment contracts are strongly efficient, but a more surprising result is that the simple supply/demand model is not rejected by the data either. Estimates of the latter suggest that the demand for teachers is inelastic and that the supply curve is slightly upward sloping, rather than perfectly elastic, at the union wage.